TWO-DIMENSIONAL CONVECTION WITH A SELF-LUBRICATING, SIMPLE-DAMAGE RHEOLOGY - Auth Ch.; Bercovici D.; Christensen U.R. (My University, 2003)
We present 2-D simulations of convection in the Earth's mantle with temperature and damage-dependent viscosity in a basally heated system. The equation governing the temporal evolution of damage includes a source term for damage, a healing term and an advection term. A systematic study of the influence of the different damage terms on the convection pattern shows that: (1) at least four different convective regimes can be distinguished depending on the size of the damage source term and (2) self-lubricating behaviour is possible only if the advection term in the damage equation is small enough compared with the other terms. We also demonstrate, that good plate-like behaviour in terms of (a) focused low-viscosity bands (LVB), (b) homogeneous surface velocities within the plates and abrupt velocity jumps across the plate boundaries and (c) asymmetric subduction, can be obtained with this kind of rheology, although an increase in subduction asymmetry tends to make convection highly time-dependent.
Keywords: LITHOSPHERIC DEFORMATION; MANTLE CONVECTION; PLATE TECTONICS